TEACHING LOAD IN THE LIGHT OF INTERNATIONAL EXPERIENCE - Dmitriy Yu. Raychuk (Высшее образование в России)
The article considers the factors promoting development of Russian universities in various areas such as improving the educational activity efficiency, development of research, the use of distance learning (MOOC), the formation of required competences of graduates. The article aims at formulating one of the conditions for solving these tasks. An important consequence of this decision will, in particular, the real wage increase of teaching personnel. An excessive auditorium workload of lecturers hampering the development of universities in the above mentioned areas can be radically reduced by means of the assimilation by Russian universities of the global practice oriented towards students' self learning managed and controlled by professors. The originality of this approach lies in the destruction of well-established in the Russian higher education stereotype, which binds the long overdue reduction of teaching load with an increase of the number of faculty staff and a decrease of student/ teacher ratio.